2004
DOI: 10.1093/jac/dkh046
|View full text |Cite
|
Sign up to set email alerts
|

Multiple effects of green tea catechin on the antifungal activity of antimycotics against Candida albicans

Abstract: These results indicate that EGCg enhances the antifungal effect of amphotericin B or fluconazole against antimycotic-susceptible and -resistant C. albicans. Combined treatment with catechin allows the use of lower doses of antimycotics and induces multiple antifungal effects. It is hoped that this may help to avoid the side effects of antimycotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
126
2
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(146 citation statements)
references
References 27 publications
7
126
2
8
Order By: Relevance
“…A number of flavonoids have been shown to possess favorable antifungal activity; however, most of them including KAE barely achieve satisfactory antifungal effect in vitro when used alone. Intriguingly, they can enhance the antifungal activities of traditional agents (such as FLC) against fluconazole-resistant C. albicans and other non-Candida albicans Candida (NCAC) species, as demonstrated by several authors (Hirasawa and Takada 2004;da Silva et al 2014). There have already been enough evidences to support the involvement of efflux pump in the antifungal mechanism of action of KAE.…”
Section: Discussionmentioning
confidence: 96%
“…A number of flavonoids have been shown to possess favorable antifungal activity; however, most of them including KAE barely achieve satisfactory antifungal effect in vitro when used alone. Intriguingly, they can enhance the antifungal activities of traditional agents (such as FLC) against fluconazole-resistant C. albicans and other non-Candida albicans Candida (NCAC) species, as demonstrated by several authors (Hirasawa and Takada 2004;da Silva et al 2014). There have already been enough evidences to support the involvement of efflux pump in the antifungal mechanism of action of KAE.…”
Section: Discussionmentioning
confidence: 96%
“…It also concluded that the combined use of EGC and low dosage of amphotericin-B inhibited the growth of C. albicans, and the action was proved to be fungicidal [20].…”
Section: Mohan Et Almentioning
confidence: 97%
“…Catechins from green tea have been reported to have antibacterial [12][13][14][15] , antifungal [16][17][18] , antiviral [19][20][21][22] and protein-denaturing 13,14,23,24) properties. The biological activities of these catechins are significantly influenced by such structural difference.…”
Section: Mutans or Streptococcus Sobrinus (S Sobrinus)mentioning
confidence: 99%